PENYULUHAN TENTANG MENYIKAPI REALITAS MULTIKULTURIS YANG TERJADI PADA MA’HAD AL-ZAYTUN DI YAYASAN GLOBAL MULIA INSANI TANGGERANG - Rahim, Abdur; Haritsah, Azra Al; Padilah, Fatur; Suwarno, Suwarno; Riyanto, Riyanto; Daryino, Daryino; Soleh, M.; Basaip, Umar (Jurnal Abdimas Bina Bangsa, 2024)
Studies on multiculturalism in Indonesia generally focus more on goals than on the process of achieving them. They emphasize the importance of tolerance, mutual respect, maintaining harmony, respecting differences, and so on. Ma'had Al-Zaytun is a modern Islamic boarding school which has students from various cultural, ethnic and regional backgrounds. This diversity gave rise to a multicultural reality which was addressed appropriately by the leadership of Ma'had Al-Zaytun, Sheikh Panji Gumilang. This can be an example for society to be able to realistically respond to multiculturalism in Indonesia. Community Service activities aim to understand community awareness about responding to the multicultural reality in Indonesia, especially what is happening in Ma'had al-Zaytun. The method used to convey this understanding is through outreach to the community specifically for administrators and members of the Global Mulia Human Foundation about multiculturalism in Indonesia. The result of this activity is that the community gets clear information to address multicultural realities and can implement it into everyday life. The form of coaching that is considered the most realistic is none other than providing provision through the delivery of learning materials and activities that are considered useful for the administrators and members of the Global Mulia Human Foundation. The Community Service Student Creativity Program is a means for students to carry out community service. The implementation of community service uses the face-to-face learning method delivered by the presenter